Effect of stocking density and genetic group on mineral composition and development of long bones of broilers - Oliveira, Andréia Fróes Galuci; Bruno, Luís Daniel Giusti; Martins, Elias Nunes; Garcia, Elis Regina de Moraes; Monteiro, Ana Carolina; Leite, Meiby Carneiro de Paula; Pozza, Paulo César; Sangali, Cleiton Pagliari (Semina: Ciências Agrárias, 2014)
The objective of this experiment was to evaluate the mineral composition, volume, bone breaking strenght and optical radiographic density of long bones (humerus, tibia and fêmur) of broiler chickens from three genetic groups and two rearing densities. The experimental design was a splitj-splot where the main plots were a combination of three genetic groups (Isa Label JA57, Ross 308 and Hybro PG) and two rearing densities ( 10 and 16 birds/m2) in a factorial arrangement, and age was considered a secondary plot, so there was six treatments with 5 replications per each treatment, totalizing 30 experimental units. The results founded showed that there were no differences in the studied genetic groups when submitted to two rearing densities for all evaluated parameters, with exception for bone breaking strength of tibia from Isa Label JA57. Bone volume increased with broiler age, while bone breaking strength and bone density showed a decreased from 28 to 35 days of age. Bone mineral content for all treatments showed up growing in the first three weeks, decreasing in the end of the experimental period. The pattern of bone development was the same for all genetic groups, despite the rearing density used, showing that broilers had a standard bone growth curve that is not affected by genetic or rearing density.